2021
DOI: 10.1371/journal.pone.0260552
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HIV status and retinol on immunogenicity to oral cholera vaccine in adult population living in an endemic area of Lukanga Swamps, Zambia

Abstract: Background We set out to assess the impact of human immunodeficiency virus (HIV) and micronutrient deficiency as indicated by serum retinol levels on the immune responses to Oral Cholera Vaccine (Shanchol™) in a cohort of participants in Lukanga Swamps, Zambia. Cholera remains endemic in Zambia with vaccines being the only effective preventive measures. However, the effect of these vaccines on populations living with HIV has not been widely documented. Methods HIV testing and confirmation was done using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Vibriocidal activity in both naïve and revaccinated adults living with HIV was also assessed, and found that, similar to the results previously reported [3], persons living with HIV had slightly lower titres when compared to their counterparts. These findings were similar to other studies [21].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Vibriocidal activity in both naïve and revaccinated adults living with HIV was also assessed, and found that, similar to the results previously reported [3], persons living with HIV had slightly lower titres when compared to their counterparts. These findings were similar to other studies [21].…”
Section: Discussionsupporting
confidence: 83%
“…Generally, vibriocidal antibody titers remain an indirect surrogate marker for longerterm immunity [14,15]. And in Zambia, the recently established vibriocidal assay is one of the reliable assays that is being used to measure cholera-specific antibodies in different scenarios [1][2][3][4]. Undoubtably, for the assessment of mucosal immunity, they certainly are a good proxy [16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations